Standardization of an organic DNA extraction method from dried blood spots and its downstream molecular applications for neonatal screening and diagnostic confirmation of lysosomal disorders - Brinckmann Oliveira Netto, Alice; Rojas Málaga, Diana; Kubaski, Francyne; Brusius Facchin, Ana Carolina; Giugliani, Roberto (Clinical and Biomedical Research, 2023)
Introduction: Dried blood spot (DBS) samples have been used for diagnostic purposes since its introduction for the neonatal screening of phenylketonuria almost 50 years ago. From that time onwards, the range of its applications has been extended until today, including next-generation sequencing (NGS) for molecular genetics diagnosis. This study aimed to evaluate a standardized organic method to extract DNA from DBS samples, for its use in the diagnostic setting. Methods: The clinical applicability of the method was tested using three samples collected in a newborn screening project for lysosomal storage diseases, allowing the determination of the genotype of the individuals. DNA was extracted from three 3-mm diameter DBS punches. Quality, purity, and concentration were determined, and its performance was assessed through standard PCR, Restriction Length Polymorphism, Sanger sequencing, and Targeted Next-generation sequencing (TNGS). Results: Results were compared with the ones obtained with DNA samples extracted following the internally validated in-house extraction protocol that used six 3-mm punches of DBS and samples extracted from whole blood. Conclusion: This organic method proved to be effective in obtaining high-quality DNA from DBS, being compatible with several downstream molecular applications, in addition to presenting a lower cost per sample.